ANALYSIS OF MOTHER'S KNOWLEDGE AND WORK BY GIVING EARLY WEANING FOOD IN TIRTOUDAN VILLAGE, PESANTREN DISTRICT, KEDIRI CITY - Miftakhur Rohmah; Riza Tsalatsatul Mufida; Shanty Natalia; Lidwina Kaka Matutina (Universitas STRADA Indonesia, 2023)
Complementary food for breast milk (weaning food) is very important to give to babies after 6 months of age. because breast milk no longer provides the nutrients the baby needs. Almost all babies aged before 6 months are given complementary foods with breast milk. The aim of this research is to analyze the relationship between maternal knowledge and work and the provision of complementary breast milk (weaning food) from an early age. This research uses a cross-sectional research design. The population in this study were all mothers who had babies 6-12 months in Nusa Indah Tirtoudan Village, Islamic Boarding School District, Kediri City, totaling 33 respondents. The sample used was simple random sampling. The data used in this research was collected using a questionnaire and then analyzed using logistic regression analysis.